The Damages and Effects Suffered by The City of Zliten and Its Residents During The Italian Invasion Between The Years 1911-1943 - Alteer, Zahra A. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
The city of Zliten has been distinguished by the characteristics that have made it a target for colonizers throughout history, including the Italian colonization, which was able to control it as part of the coastal cities in 1912. They left after fierce battles such as the Battle of Wadi Majer in the Majer area in Zliten in 1915, and the Battle of Al-Qardabiya in the same year, after which they left Libya. Then regained control of the city on February 23, 1923, after several battles on its land. The enemy's control had severe consequences on the city and its inhabitants, as it caused damage in various aspects. The city was subjected to brutal bombing by the enemy and suffered from the brutal and inhumane practices of the occupation, like other cities that were affected by the hands of the brutal colonizer. When they occupied the city of Al-Khums, they did not hesitate to strike it by air and sea to relieve their besieged forces and weaken the strength of the besieged fighters. They also deployed their forces in Zliten to occupy some internal areas، as they did when they occupied the city of Wurfla. They committed heinous acts against the citizens in a cowardly and bloody manner. They established military courts that issued unjust judgments in the field without trial. The city was filled with grief and mourned the loss of many of its sons, including martyrs, prisoners, exiles, migrants, and displaced people. Fake judgments were issued against them, their properties were confiscated, and their farms were destroyed. The colonizer took control of maritime and land trade routes, and with the participation of the population in the battles, agriculture, animal production, and industry were neglected, poverty, oppression, and deprivation spread, and diseases proliferated. This harmed the city in all fields and aspects. His brutal practices were not limited to people but extended to religious institutions and the struggle of religious leaders. Their books and scientific heritage were desecrated and burned، and religious men and places of worship were forced to migrate. The colonizer made great efforts to empty the city of its people، especially the wise and intellectuals، to settle the displaced and control its resources.
Keywords: Zliten; Italian colonialism; Damage; Jihad